To the end of the land - Grossman, David (Alfred A. Knopf, 2010)
Ora, a middle-aged Israeli mother, is on the verge of celebrating her son Ofer's release from army service when he returns to the front for a major offensive. she sets out for a hike in the Galilee, leaving no forwarding information for the "notifiers" who might darken her door with the worst possible news. Recently estranged from her husband, Ilan, she drags along their former best friend and her former lover Avram. Avram served in the army alongside Ilan when they were young. Avram was sent into Egypt and the Yom Kippur War, where he was brutally tortured as POW. In the aftermath, a virtual hermit, he refused to keep in touch with the family and has never met the boy. Ora supplies the whole story of her motherhood, a retelling that keeps Ofer very much alive and opens Avram to human bonds undreamed of in his broken world.